The influence of response timeliness and work motivation on service quality and its influence on the number of patient visits at serang city regional hospital - Ratu Pipit Kurnia Fitri; Abdul Malik; Asep Unang Rusmana; Jhon Chaidir; Haerofiatna Haerofiatna (Institute of Computer Science (IOCS), 2026)
This study aims to examine the influence of response time accuracy and work motivation on service quality, as well as the effect of service quality on the number of patient visits at the Regional Public Hospital of Serang City. A quantitative research approach was employed to achieve these objectives. The data analysis technique used was multiple regression analysis to measure the relationships between response time accuracy and work motivation with service quality, and subsequently the effect of service quality on patient visits. The research population consisted of 7,669 individuals associated with the Regional Public Hospital of Serang City. Using a disproportionate stratified random sampling technique, a total of 381 respondents were selected as the research sample. The results of the study indicate that response time accuracy accounts for 15.98%, work motivation for 22.89%, service quality for 20.12%, and patient visits for 20.40%. Furthermore, the magnitude of the influence of response time accuracy on service quality is 0.285, while the influence of work motivation on service quality is 0.281. In addition, service quality has an influence of 0.519 on the number of patient visits. These values indicate that the effects fall within the low to moderate category. The hypothesis testing results show that response time accuracy and work motivation jointly influence service quality with a hypothesis acceptance level of 11.4%. Meanwhile, the joint influence of response time accuracy and work motivation on patient visits reaches a hypothesis acceptance level of 20.7%.